The betrayed - Wheeler, Jeff, 1971- (Wheeler, Jeff, 1971- Dawning of Muirwood, 2023)
"To retrieve an ancient stolen tome, which holds the secrets of immortality, from the clutches of the Queen of Brythonica, Eilean engages in a duel of wits and magic to save one world to secure the future for which she is destined in her own"--